2019
DOI: 10.31965/dtl.v1i1.355
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Tingkat Kejadian Karies Gigi (DMF-T) antara Laki-Laki dan Perempuan Usia 12-14 Tahun

Abstract: Differences in the incidence rate of dental caries (DMF-T) between men and women aged 12-14 years. Dental and oral health is the well-being of the oral cavity which enables a person to communicate effectively, enjoy various foods, be confident, and improve a better quality of life. Poor dental and oral health can result in disruption of masticatory function due to tooth malfunction. One form of tooth decay is dental caries. The purpose of this study was to determine the incidence of dental caries (DMF-T) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…By contrast, boys seem to place less emphasis on beauty, cleanliness, and grooming because in general they are prone to violent behavior, destruction and chaos. 19 The level of dental caries by age showed that most respondents in our study had dental caries levels that were in the very high category in the 7-year age group. Our findings are in line with those of research conducted by Mayasari which found that children aged 7 years have a very high caries incidence rate with 18 children.…”
Section: Discussionmentioning
confidence: 51%
“…By contrast, boys seem to place less emphasis on beauty, cleanliness, and grooming because in general they are prone to violent behavior, destruction and chaos. 19 The level of dental caries by age showed that most respondents in our study had dental caries levels that were in the very high category in the 7-year age group. Our findings are in line with those of research conducted by Mayasari which found that children aged 7 years have a very high caries incidence rate with 18 children.…”
Section: Discussionmentioning
confidence: 51%